2017
DOI: 10.1093/ckj/sfx113
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the management of the haemodialysis-related arteriovenous fistula following kidney transplantation

Abstract: Arteriovenous fistula (AVF) is regarded as the best vascular access for chronic haemodialysis (HD). Still, AVF inherently causes significant haemodynamic changes. Although the necessity for vascular access despite its putative cardiovascular complications favours AVF creation in patients under chronic HD, one may question whether sustaining a functional AVF after successful kidney transplantation extends the haemodynamic threat. Small prospective series suggest that AVF ligation causes rapid and sustained redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 62 publications
0
15
0
5
Order By: Relevance
“…Highflow fistulas are regularly closed when aneurysm with concomitant risk of rupture, steal syndrome with acral ischaemia, and/or congestive heart failure at NYHA stage Am J Nephrol 2020;51:511-519 DOI: 10.1159/000508957 III or IV are present. However, both in the presence and absence of typical clinical ligature indications, there is great variety in routine clinical management [14]. With respect to own retrospective data [6] showing up to 25% occurrence of high-output heart failure with consecutive closure of fistulas, we conducted a prospective randomized controlled trial evaluating the potential benefit of prophylactic ligature of high-flow AV fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Highflow fistulas are regularly closed when aneurysm with concomitant risk of rupture, steal syndrome with acral ischaemia, and/or congestive heart failure at NYHA stage Am J Nephrol 2020;51:511-519 DOI: 10.1159/000508957 III or IV are present. However, both in the presence and absence of typical clinical ligature indications, there is great variety in routine clinical management [14]. With respect to own retrospective data [6] showing up to 25% occurrence of high-output heart failure with consecutive closure of fistulas, we conducted a prospective randomized controlled trial evaluating the potential benefit of prophylactic ligature of high-flow AV fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the general non-transplant population, the creation of a pre-dialysis AV access has been recently suggested to delay ESKD progression [1316]. Due to the lack of consistency across studies, there is no consensus on the causal link between AV access creation and the progression of ESKD and heart disease [3, 4].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, another study of 285 KTRs reported that the closure of a functioning AVF for KTRs with stable kidney allograft function significantly accelerated eGFR decline over a consecutive 12-month period after KT [3]. As a whole, the current management of a functioning AV access (surgical closure versus watchful preservation) for KTRs with stable kidney allograft function remains controversial and does not rely on robust evidence-based data [4, 28]. The individual risk of allograft dysfunction and a return to chronic dialysis need to be considered [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-transplant, vascular access may be challenging because of previous vein thromboses and collateralization whilst at the same time vascular access should be preserved, especially in patients at risk of transplant failure. This includes the avoidance of subclavian lines if possible and the preservation of existing AVFs [10].Femoral venous access on the side of the graft should be avoided whenever possible.…”
Section: Preserve Vascular Accessmentioning
confidence: 99%